TikTok Analysis as a Learning Media and Activism Instrument - Alexandro, Rinto; Hariatama, Fendy; Uda, Tonich (Universitas Pendidikan Ganesha, 2022)
In this new era of social media development, many explain that the existence of social media can only be toxic and have a terrible impact on children's brain development. However, on the other hand, many people often do not realize the positive impact of social media on children. This study aims to analyze TikTok as a learning media and activism tool which will be studied further using social media interaction theory. This research is qualitative. The method used in collecting data is descriptive-analytical. This research was designed using phenomenology, which has methodological characteristics. Data collection techniques are observation, interviews, digital documentation, and using instruments. The technique used to analyze the data is descriptive qualitative analysis. The research results are that TikTok is a social media platform that can be used for educational purposes as well as activism among millennials and Generation Z. Various TikTok hashtags that lead to learning and advocacy movements are evidence of this movement. TikTok, according to the researchers, may be a valuable platform for today's youth population.